P83FAs mediate cardiac hypertrophic response to exercise. (15th July 2014) - Brix, S; Foryst-Ludwig, A; Salatzki, J; Januszewicz, E; Rothe, M; Kershaw, E; Kintscher, U
Abstract: We have previously showed that both exercise-induced lipolytic activity in adipose tissue and cardiac hypertophic response to training were significantly reduced in adipose tissue specific -ATGL-KO mice (atATGL-KO) mice. It was accompanied by the absence of plasma fatty acid increases in those mice. To identify the underlying mechanisms of physiological cardiac hypertrophy mediated by variations of plasma lipid concentrations in atATGL-KO mice, we performed a comprehensive analysis of circulating lipid species using Rapid Resolution HPLC/ Tandem MS. Selected fatty acids, such as C16:1 (palmitoleic acid), were increased in trained wt mice but not in atATGL-KO mice, whereas others were similarly regulated in both genotypes. To investigate the role of FAs in vitro we stimulated murine cardiomyocytic HL-1 cells with a FA-mixture containing C14:0, C16:0 and C16:1 (equimolar concentrations as determined in post-exercise serum), or with C16:1 alone, and analyzed cellular hypertrophy. The FA-mixture, and more importantly, C16:1 alone effectively induced cardiomyocyte hypertrophy in exercise-relevant plasma concentrations, suggesting that C16:1 liberated from adipose tissue serves as molecular mediator of training-induced cardiac hypertrophic. Moreover, the mRNA expression of the atrial natriuretic factor (ANF) and beta-cardiac myosin heavy chain isogene (beta-MHCH), both markers of pathological hypertrophy, was not increased under C16:1-stimulation. Collectively, our data provide the first evidence that the adipose tissue – heart crosstalk involving AT-lipolysis, cardiac FA-uptake, and FA-mediated cardiac hypertrophy determines the morphological adaptation of the exercising heart. Palmitoleic acid, released from adipose tissue in an ATGL-dependent manner, serve as molecular mediators of exercise-induced cardiac hypertrophy.